Integration of Technology in Islamic Religious Education - Sedya Santosa (AT-TAKILLAH : Jurnal Pendidikan dan Keislaman, 2025)
The rapid advancement of technology has transformed educational practices worldwide, offering new opportunities for enhancing teaching and learning processes. Islamic Religious Education (IRE), or Pendidikan Agama Islam (PAI), traditionally relies on conventional methods such as lectures, memorization, and discussion. However, integrating technology into IRE has the potential to create more engaging, interactive, and meaningful learning experiences while supporting the internalization of Islamic values. This study aims to explore the strategies, practices, and challenges of integrating technology in IRE to improve students’ understanding of Islamic teachings and promote moral and spiritual development. A qualitative research design was employed in this study, involving classroom observations, semi-structured interviews with IRE teachers, and document analysis of lesson plans and teaching materials. Participants were selected through purposive sampling from Islamic-based schools where technology is actively used in teaching. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, with triangulation of multiple data sources to ensure validity and reliability. The findings indicate that technology integration in IRE is implemented through the use of multimedia content, interactive activities, and digital platforms. Multimedia presentations, educational videos, and interactive quizzes were found to increase student engagement and motivation, while digital tools facilitated collaborative learning and self-directed exploration of Islamic teachings. Teachers deliberately selected and adapted materials to ensure alignment with Islamic values, emphasizing principles such as honesty, discipline, responsibility, respect, and cooperation. Classroom routines, teacher modeling, and value-based activities further reinforced the internalization of these values. Despite these benefits, challenges were identified, including limited access to devices and internet connectivity, varying levels of digital literacy among teachers and students, and the need for appropriate digital resources that integrate Islamic values. Addressing these challenges requires professional development for teachers, provision of value-oriented digital teaching materials, and strategies to ensure equitable access to technology in educational settings. In conclusion, the integration of technology in Islamic Religious Education enhances students’ learning outcomes, engagement, and moral development. Thoughtful and deliberate implementation of digital tools enables teachers to deliver lessons that are both interactive and aligned with the ethical and spiritual objectives of IRE. This study highlights the potential of technology to transform Islamic education into a holistic, value-oriented learning experience that balances cognitive, spiritual, and moral growth, preparing students to navigate the modern world with knowledge, skills, and ethical integrity.